Unlocking Carbon Reduction Potential of Digital Trade: Evidence from China’s Comprehensive Cross-border E-Commerce Pilot Zones - Gao, Da; Tan, Linfang; Chen, Yue (SAGE open, 2025)
As an important driving force for economic growth, digital trade provides opportunities for urban green development. Using city-level data in China from 2005 to 2020, we take the cross-border e-commerce comprehensive pilot zone (CBEC) as a policy shock to construct a spatial difference-in-difference (SDID) model, which is adapted to quantitatively examine the carbon reduction effects and impact mechanisms of CBEC policy. The results confirm that the implementation of CBEC policy significantly reduces the carbon emissions (CE) of pilot cities about 4.5%, mainly due to resource allocation efficiency promotion, industrial structure upgrading, and green technology boosting. Meanwhile, there is a significant spatial spillover effect, resulting in a 3.9% CE decrease in the neighboring cities. In addition, the CBEC policy has a more significant CE reduction effect in resource-based and high-degree information cities. Our results provide evidence for the economic effect of digital trade and accelerate green development in cities.